2003
DOI: 10.1345/aph.1c320
|View full text |Cite
|
Sign up to set email alerts
|

Combined Furosemide and Human Albumin Treatment for Diuretic-Resistant Edema

Abstract: Published studies report conflicting results regarding the efficacy of combined furosemide and albumin. Although it is difficult to generate firm conclusions, it appears the combination may provide clinical benefits for select patients. Given these findings, we believe that the addition of albumin to enhance diuretic efficacy should be reserved for patients with recalcitrant edema or ascites in whom diuretic doses have been maximized and those with severe hypoalbuminemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…In that regard, it is noted that Agarwal et al (2) showed that displacing furosemide from plasma proteins with a sulphonomide (sulfisoxazole) did not correct resistance in nephrotic patients. There is still controversy about whether and how albumin infusion could increase the natriuretic actions of furosemide in the nephrotic state (45). Taken together, diminished reabsorption, increased T½, and high-grade proteinuria in patients with CKD could limit the natriuretic response.…”
Section: Does Kidney Disease Affect the Actions Of Furosemide?mentioning
confidence: 99%
“…In that regard, it is noted that Agarwal et al (2) showed that displacing furosemide from plasma proteins with a sulphonomide (sulfisoxazole) did not correct resistance in nephrotic patients. There is still controversy about whether and how albumin infusion could increase the natriuretic actions of furosemide in the nephrotic state (45). Taken together, diminished reabsorption, increased T½, and high-grade proteinuria in patients with CKD could limit the natriuretic response.…”
Section: Does Kidney Disease Affect the Actions Of Furosemide?mentioning
confidence: 99%
“…The reasons proposed for the lack of patient response to diuretics include a decreased delivery of the diuretics into the tubular lumen, hypoalbuminemia, and binding of the diuretics to urinary albumin. Lack of compliance with oral medications, impaired bioavailability, and reduced glomerular filtration rate also lead to a suboptimal response to diuretics [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of hypoalbuminemia to impaired diuretic responsiveness can be overcome by administering larger doses of loop diuretics, either orally or intravenously (IV) [8][9][10][11]. This approach results in the excretion of a larger amount of the drug in the urine and, consequently, a greater natriuretic response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this combination should be reserved for specific groups of patients whose doses of diuretics have been maximized or for cases of severe hypoalbuminemia. 17 The findings from the review by Caraceni et al 34 show that use of human albumin alone for correcting hypoalbuminemia is not backed by scientific evidence. This confirms the stance taken in the guidelines, i.e.…”
Section: Discussionmentioning
confidence: 99%